The Role Of Decision-Making Speed, Managerial Competence, And Risk Management On Firm Performance - Irzan Soepriyadi; Junias Robert Gultom; Triyono Adi Tristanto; Hamdiah (Malaqbi Publisher, 2026)
This study seeks to investigate the effect of decision-making speed, managerial effectiveness, and risk management on firm performance. It is noted that in this contemporary business world, which is characterized by rapid changes and stiff competition, it is mandatory for companies to improve their internal competencies in order to perform better. This study uses a quantitative research methodology where data were collected using a cross-sectional survey design. The study used managerial effectiveness, decision-making speed, and risk management as independent variables and firm performance as the dependent variable. It is observed from the results that the speed of decision making, the competence of management, and risk management all have a positive impact on firm performance. Out of these three variables, the competence of management plays a prominent role, while speed of decision making and risk management play secondary roles. Additionally, the results show that the mentioned three variables together explain a significant portion of variance in firm performance, signifying their joint significance in achieving success. Moreover, it has been shown that these three variables are interconnected as the competence of management affects decision-making, and risk management facilitates better decision-making. The current study is an addition to the existing body of literature in that it provides a holistic analysis of the relationship between decision-making speed, managerial capability, risk management, and organizational performance. Based on the empirical results presented in the study, there is potential for practical use that could be applied to organizations. Improvements in each of these aspects mentioned can help achieve better organizational performance. Therefore, it can be concluded that it is essential for organizations to have a holistic perspective towards their management.